The knowledge and practices of mothers regarding exclusive breastfeeding in the Mahwelereng Local Area of the Waterberg District, Limpopo Province - Frans, Raesetja Annah (My University, 2014)
The aim of this study was to determine the knowledge and practices of mothers with regard to exclusive breastfeeding in the Mahwelereng Local Area of the Waterberg District, Limpopo Province. A quantitative study was conducted by using a researcher-administered structured questionnaire at six clinics in the Mahwelereng Local Area. A simple random sampling method was used to select the hundred and seventy five mothers who had babies of less than six months old from whom data was collected. Data was analysed with the assistance of the statistician by using the SPSS software program. Data is presented applying descriptive and inferential statistics. Less than half (74; 42.3%) of the responding mothers were practising exclusive breastfeeding despite the fact that 137 (78.3%) of them were given information about exclusive breastfeeding. There is an association between knowledge of exclusive breastfeeding (Chi-Square= 14.039; Sig=0.000 p<0.05) and exclusive breastfeeding practice. There is no association between exclusive breastfeeding practice and HIV status (Chi-Square=2.444; Sig=0.118; p>0.05). Challenges that mothers faced in relation to practising exclusive breastfeeding were work-related, school-related, health-related, pressure from family to mix-feed, and a lack of knowledge. However, 42.9% of the respondents indicated that they did not have any challenges with regard to the practice of breastfeeding. It was, therefore, recommended that one-on-one counselling about exclusive breastfeeding needs to be intensified and maternity leave should be extended to six months. The majority of respondents showed adequate knowledge of what exclusive breastfeeding was because they were counselled about breastfeeding although they were not practising it. Key words: Exclusive breastfeeding, mothers, knowledge, practices, mix-feeding.
Thesis (MPH. ) --University of Limpopo, 2014
Keywords: Exclusive breastfeeding; Mix-feeding; 649.33; Breastfeeding -- South Africa -- Limpopo; Bottle feeding